?A STUDY OF POTENTIAL LABELS FOR FLUORESCENT DERIV ATISA TION REACTIONS WITH PROTEINS - AMINUDDIN, M.; MILLER, J.N. (Biological Sciences - PJSIR, 1995)
The suitability of the newly synthesised polycylic aromatic dialdehydes as labelsto form fluorescent derivatives has been examined. The fluorescence properties of the derivatives such as the reaction time, stability, antigen- antibody reaction and inrierfiltereffect havebeen investigated. The change in fluorescence properties of the labelled protein forms the basis of a fluorescence method for the determination of biotin.